1997
DOI: 10.1007/s004420050068
|View full text |Cite
|
Sign up to set email alerts
|

Linking breeding and wintering grounds of neotropical migrant songbirds using stable hydrogen isotopic analysis of feathers

Abstract: Recent studies have shown that stable hydrogen isotope ratios (δD) in the tissues of animals often correlate with δD of local precipitation. Here we examined the relationship between δD in feathers and growing season precipitation for neotropical migrant songbirds breeding over a continent-wide isotopic gradient. δD values were determined on feathers of 140 individuals of 6 species of wild insectivorous forest songbirds (Setophaga ruticilla, Empidonax minimus, Vermivora peregrinus, Catharus ustulatus, Seiurus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
467
5
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(496 citation statements)
references
References 35 publications
19
467
5
5
Order By: Relevance
“…The stable isotope signature of feather keratin has been used to document the feeding behavior and migratory patterns of various species of birds (Mizutani and Wada 1988;Mizutani et al 1990Mizutani et al , 1992Clark 1992a, 1992b;Chamberlain et al 1997;Hobson and Wassenaar 1997;Marra et al 1998). Feathers provide an optimal tissue for the study of endangered species because they represent a non-lethal source tissue that may be collected without invasive handling.…”
Section: Stable Isotopes As Tracers Of Life History Informationmentioning
confidence: 99%
“…The stable isotope signature of feather keratin has been used to document the feeding behavior and migratory patterns of various species of birds (Mizutani and Wada 1988;Mizutani et al 1990Mizutani et al , 1992Clark 1992a, 1992b;Chamberlain et al 1997;Hobson and Wassenaar 1997;Marra et al 1998). Feathers provide an optimal tissue for the study of endangered species because they represent a non-lethal source tissue that may be collected without invasive handling.…”
Section: Stable Isotopes As Tracers Of Life History Informationmentioning
confidence: 99%
“…Hobson et al (13) provided evidence that ␦ 2 H values of drinking water were incorporated into different proteinaceous tissues of quail, although no mechanistic basis was proposed for this relationship. The ␦ 2 H values of bird feathers and butterfly wings (both are largely keratin) and water in the region in which the tissue was produced are highly correlated (14,15). Kreuzer-Martin et al (1) showed that Ϸ70% of the oxygen and Ϸ30% of the hydrogen atoms in microbial spores (Ϸ50% proteinaceous) were derived from the water in the growth medium, whereas the remainder was derived from the organic compounds supplied as substrate (16).…”
mentioning
confidence: 99%
“…C or N). [8][9][10][11][12][13][14] A number of studies have also used variation in 18 O to track animal movements, typically using inorganic materials (e.g. teeth 15,16 ).…”
mentioning
confidence: 99%